Sustainable ocean development policies in Indonesia: paving the pathways towards a maritime destiny - Wuwung, Lucky; McIlgorm, Alistair; Voyer, Michelle (Frontiers in Marine Science, 2024)
Maritime countries, including Indonesia, have indicated their interest in developing a national ocean policy and blue economy plan to boost economic growth while promoting sustainability in and from oceanic activities. In 2017, the Government of Indonesia published the Indonesian Ocean Policy (IOP), the first of its kind since independence, and subsequently developed a series of blue economy documents as an integral part of its national development agenda whilst also indicating its support for the global sustainability objectives stipulated in the 2015 Sustainable Development Goals (SDGs). However, development obstacles such as: declining ocean health; climate crises; fragmented ocean management; inadequate infrastructure and technology; limited data support; low sustainable investment; and the blurred definition of the blue economy, pose risks to successful outcomes of sustainable ocean development in Indonesia. When unaddressed, these challenges can inhibit the policy’s effectiveness in delivering its intended outcomes. This qualitative study explores Indonesia’s interests in sustainable ocean development and how it pursues them while advancing economic objectives and commitments towards SDGs and net zero emission targets. The study finds that maintaining ocean health and ensuring sustainable use of ocean resources are Indonesia’s most vital interests for sustainable ocean development. The national ocean policy and the blue economy have been employed as two successive and simultaneous avenues to pursue Indonesia’s maritime interests. Unfortunately, to date, both approaches have yet to obtain maturity and ocean affairs are overshadowed by other national development priorities. By focusing on ocean governance and its development in the contemporary context, this article sheds light on the important role of policymaking in modern-day ocean governance. A cautious approach to policy design is crucial to avoid common pitfalls in sustainable ocean development, such as weak implementation strategies and the consequent failure to meet core sustainability objectives.